SPATIAL MAPPING OF CORAL REEF DISTRIBUTION IN KARIMUNJAWA ISLAND USING LYZENGA ALGORITHM - Hidayat, Esa Fajar; Hanafi, Faisal; Purwanto, Hery; Noraini, Alifah; Marsela, Kristina; Dewi, Atika Kumala; Lubis, Muhammad Zainudin (Hasanuddin University, 2025)
Coastal areas have high ecosystem productivity and are characterized by abundant fish species and coral reefs. However, these ecosystems are vulnerable to environmental pressures caused by human activities and natural dynamics. Coral reefs, consisting of organisms from the class Anthozoa within the order Scleractinia, which produce calcium carbonate structures, are key indicators of coastal ecosystem health. Coral reefs share biological characteristics with soft corals, hydras, and sea anemones as part of the phylum Cnidaria. Their existence is highly sensitive to environmental changes, whether natural or anthropogenic. In Indonesia, coral reef conditions have experienced significant degradation, with 36.18% in the damaged condition, only 6.56% categorized as very good, and 22.96% as good. The remaining 34.3% fall under the poor category, particularly around Karimunjawa and Kemujan Islands. Accurate data-based monitoring and management are essential for conserving these ecosystems. One method used to map and analyze coral reef distribution is the Lyzenga algorithm, which can distinguish shallow-water characteristics from coral reef habitats using satellite imagery. In this study, the Lyzenga algorithm was applied to SPOT 6 imagery for the Karimunjawa and Kemujan regions, covering an area of 8.46 km². The results showed that live coral reefs cover approximately 46% of the area, while dead coral reefs account for 56%, indicating a level of degradation that requires further attention in conservation and ecosystem recovery strategies. This study highlights the critical state of coral reefs in Indonesia, particularly in the Karimunjawa and Kemujan regions, emphasizing the necessity for conservation efforts driven by precise monitoring techniques such as the Lyzenga algorithm.